Synthesis of stable γ-phase MnS1−xSex nanoflakes with inversion symmetry breaking. Issue 45 (11th November 2022) - Zheng, Bo; Fu, Jun; Zhu, Yuanmin; Liang, Jing; She, Yongzhi; Xiang, Junxiang; Ma, Xiang; Zhang, Ying; Wang, Shasha; Hu, Guojing; Zhou, Yuehui; Feng, Yan; et al.
Abstract : In this paper, we report the rational synthesis of stable γ-phase MnS1− x Se x (0 ≤ x ≤ 0.45) nanoflakes. By tuning the parameters of synthesis duration and temperature, we produced a detailed growth phase diagram. Abstract : Inversion symmetry breaking plays a critical role in the formation of magnetic skyrmions. Therefore, for the application of skyrmion-based devices, it is important to develop novel engineering techniques and explore new non-centrosymmetric lattices. In this paper, we report the rational synthesis of stable γ-phase MnS1− x Se x (0 ≤ x ≤ 0.45) nanoflakes with an asymmetric distribution of the elemental content, which persists on inversion symmetry breaking. The temperature dependence of resonant second-harmonic generation characterization reveals that a non-centrosymmetric crystal structure exists in our as-grown γ-phase MnS1− x Se x with spatial-inversion symmetry breaking. By tuning the parameters of nucleation temperature and growth time, we produced a detailed growth phase diagram, revealing a controllable as-grown structure evolution from γ-phase wurtzite-type to α-phase rock-salt type structure of MnS1− x Se x nanoflakes. Our work provides a new playground to explore novel materials that have broken inversion symmetry.